Pap Smear Cytology Results in Patients Under Visual Inspection of Acetic Acid (VIA) at Primary Health Care: Hasil Sitologi Pap Smear pada Pasien di Bawah Inspeksi Visual Asam Asetat (IVA) di Pusat Perawatan Kesehatan Utama - Ivan M. Sondakh; Bismarck J. Laihad; Eddy Suparman (Indonesian Socety of Obstetrics and Gynecology, 2019)
Abstract Objective: we compared the results of Pap Smear and VIA in Primary Healthcare Centres (PHCs). Methods: This was a descriptive study that investigated Pap smear cytology results in patients who underwent visual inspection of acetic acid in PHC for early detection of cervical cancer. This research was done in three PHCs (Tikala Baru, Tuminting and Paniki), which appointed by Manado Health Department as they have certified general practitioner, midwives, and nurse for VIA examination. The Pap smear examination was performed by researchers and VIA performed by certified PHC VIA Team using tools, equipment, available at the PHCs without intervention. Results: Of 55 subjects, 15 and 40 subjects were VIA positive and negative, respectively. Fifteen samples with positive VIA there were only three subjects with dysplasia (LSIL) results in Pap smear, and 40 samples with VIA negative there were two samples with dysplasia (LSIL) results in Pap smear. Conclusion: The result of VIA examination in primary health care with VIA positive was only 20% had dysplasia (LSIL) on pap smears, and negative VIA sample was 5% with dysplasia (LSIL) on Pap smear. Keywords:cervical cancer, pap smear, VIA. Abstrak Tujuan: membandingkan hasil pemeriksaan gambaran sitologi Pap Smear dengan hasilpemeriksaan IVA di Puskesmas. Metode:Penelitian ini merupakan penelitian deskriptif untuk mengetahui hasil sitologi Pap Smear pada pasien yang telah dilakukan pemeriksaan inspeksi visual asam asetat di fasilitas kesehatan tingkat I untuk deteksi dini kanker serviks. Penelitian ini dilakukan di tiga Puskesmas (Puskesmas Tikala Baru, Tuminting, dan Paniki) yang telah diberikan pelatihan IVA yang ditunjuk oleh Dinas Kesehatan Kota Manado. Pemeriksaan Pap Smear dilakukan oleh penelitidan IVA dilakukan oleh petugas kesehatan tingkat I dengan menggunakan alat, perlengkapan, yang tersedia di Puskesmas tanpa intervensi. Hasil :Dari 55 subyek, didapatkan 15 subyek dengan IVA positif, dan 40 subyek dengan IVA negatif. Dari 15 subyek dengan IVA positif hanya terdapat 3 orang diantara dengan hasil displasia pada Pap Smear, dan 40 subyek dengan IVA negatif terdapat 2 orang dengan hasil displasia pada Pap Smear. Kesimpulan: Hasil pemeriksaan IVA di fasilitas kesehatan tingkat I dengan IVA positif hanya 20% memliki gambaran displasia (LSIL) pada hasil Pap smear dan sampel dengan IVA negative terdapat 5% dengan gambaran displasia (LSIL) pada hasil Pap Smear. Kata Kunci: IVA, kanker serviks, pap smear.